2015
DOI: 10.1002/14651858.cd011595
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito repellents for malaria prevention

Abstract: Analysis 3.3. Comparison 3 Spatial repellents compared to placebo or no treatment, Outcome 3 Reduction in mosquito bites..... Analysis 3.4. Comparison 3 Spatial repellents compared to placebo or no treatment, Outcome 4 Adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…However, overall evidence remains inconclusive and findings of this China study particularly had very large confidence intervals because of very low number of cases, therefore, reducing the strength of the evidence [ 11 ]. Indeed, a recent Cochrane review on this subject concluded that although some studies have found a protective effect, it remains unclear if spatial repellents are effective at reducing the risk of malaria infection, and that further well-designed studies must be conducted in order to improve the certainty of evidence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, overall evidence remains inconclusive and findings of this China study particularly had very large confidence intervals because of very low number of cases, therefore, reducing the strength of the evidence [ 11 ]. Indeed, a recent Cochrane review on this subject concluded that although some studies have found a protective effect, it remains unclear if spatial repellents are effective at reducing the risk of malaria infection, and that further well-designed studies must be conducted in order to improve the certainty of evidence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…User compliance is a major limitation of most topical insect repellents [12,15,16] and since topical repellents are applied to the skin, most users prefer insect repellents which are cosmetically pleasant in terms of odour and feel on the skin; in addition to providing protection from biting insects [38]. In this study, all volunteers preferred to use MAÏA® repellent ointment compared to 20% DEET because those who applied MAÏA® repellent reported that the ointment felt better on their skin.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, deployment of topical mosquito repellents for malaria prevention is not recommended by the World Health Organization (WHO) as an intervention with public health value but maybe bene cial as an intervention to provide personal protection against malaria [13,14]. Topical repellents must be applied daily or even several times a day, and poor user compliance is a major limitation to the effectiveness of topical repellents [12,15,16]. Common reasons for poor compliance include forgetting to apply the repellent [15,17], poor acceptability including unpleasant smell or greasy "feel" on the skin [17] and the perception that repellents are poisonous [15].…”
Section: Introductionmentioning
confidence: 99%
“…This search strategy was adapted from a Cochrane Collaboration Review Protocol ("Mosquito repellents for malaria prevention -Protocol)" (77). We searched in PubMed and Embase databases.…”
Section: Fundingmentioning
confidence: 99%